Reconfiguring Qur'anic Intertextuality: Mun'im Sirry's Cross-References, Munāsabah, and Tafsīr Al-Qurʾān bi Al-Qurʾān - Afni Azzahra; Ida Kurnia Shofa; Khoirun Nidhom; Gilang Gymnastiar (Jurnal Fuaduna : Jurnal Kajian Keagamaan dan Kemasyarakatan, 2026)
This article examines Mun'im Sirry's concept of cross-references in The Qur'an with Cross-References within the broader framework of Qur'anic intertextuality. While cross-referencing has been presented as a contemporary approach to reading the Qur'an, its relationship to the classical concepts of munāsabah and tafsīr al-Qurʾān bi al-Qurʾān (TQbQ) remains insufficiently explored. This study aims to analyze the conceptual foundations, methodological characteristics, and distinctive features of Sirry's approach in comparison with these two established exegetical traditions. Employing library research with a comparative descriptive design, the study applies qualitative content analysis to Sirry's The Qur'an with Cross-References, classical works on ʿulūm al-Qurʾān, and relevant contemporary scholarship. Sūrat al-Fātiḥah serves as the primary analytical sample because of its foundational position in the muṣḥaf. The findings demonstrate that the three approaches share the same premise of Qur'anic intertextuality but differ in their interpretive orientation. Munāsabah emphasizes textual coherence, TQbQ explains one verse through another, whereas Sirry's cross-references organize thematic connections through a practical system of marginal annotations. The analysis also shows that Sirry's selection of cross-references is interpretive rather than exhaustive, reflecting specific editorial criteria. This study concludes that Sirry's cross-references represent a contemporary reconfiguration of the classical TQbQ tradition, offering greater accessibility while remaining selective in coverage and methodological transparency.